John Sergeant correspondence - Sergeant, John, 1779-1852.
Two ALsS written by Sergeant to Jonathan Meredith (1837 April 1) and Richard Smith (1840 February 7) relating to banking matters.
Lawyer, public official, and U.S. representative from Pennyslvania.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Meredith, Jonathan D., -- 1783-1872 -- Correspondence; Smith, Richard, -- of Washington, D.C. -- Correspondence; Banks and banking -- United States; Lawyers; Public officials -- Pennsylvania; Representatives, U.S. Congress -- Pennsylvania